MAIN TRENDS OF «OLD ORDER» CAPITALISM: THE DICHOTOMY BETWEEN INDUSTRIAL AND COMMERCIAL CAPITAL - Валесян, С. В. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2017)
The article examines the main essential characteristics of capitalism of pre-industrial era, the spheres of its turn over and profit accumulation logic in terms of world-system analysis. The basic strategies of capitalism over the past five hundred years are studied as well as the role of capital accumulation in the formation of international relations; market institutions functions in the modern world-system are analyzed.